Konsep Islamisasi Ilmu Mohd Kamal Hassan ( Mohd . Kamal Hassan's Concept and Framework of Islamization of Knowledge) - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Jaanur Elbarik Indonesia, 2025)
The aim of this research is to review its influence on Islamic thought that developed in Malaysia as demonstrated by the moral and spiritual idealism it brings in influencing metaphysical awareness and intellectual traditions as well as the system and basis of education in Malaysia. This study is structured based on qualitative methods, in the form of a literature review and documentary. The data obtained was analyzed descriptively, analytically, historically and synthetically to obtain accurate and scientific conclusions. The findings of the study found Prof. Kamal has made important and influential contributions in the context of awareness and strengthening the ideology of monotheism and its natural view. This study contributes to presenting the ideas he developed in the tradition of modern Islamic thought in terms of designing and implementing the effective foundations of the Islamization of science in Malaysia which include his holistic planning and approach in upholding a monotheistic view of life and bringing forth genuine aspirations and values ​​and cultural manifestations based on the theory of Islamization (Islamiyyatul ma'rifat), the unification of knowledge and values ​​(takamul al-ma'rifi) and the Islamization he introduced in the realm of thought and development. intellectuals in Malaysia